PEMAHAMAN KONSEP GEOMETRI PADA PEMBELAJARAN PROBLEM BASED LEARNING BERMUATAN ETNOMATEMATIKA BANGUNAN CAGAR BUDAYA KOTA SEMARANG - Hariyadi, Slamet; Muttaqin, Muhammad Fauzan (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2020)
ABTRACTThe purpose of this study was to describe the understanding of the geometry concept of the fourth grade students of SD Negeri Candi 01 after the implementation of a problem based learning model containing ethnomatematics. The research method used is descriptive method with a qualitative approach. The selection of research subjects was selected by purposive sampling technique based on the learning achievement of students, which were classified into three high, medium and low learning achievements. The subject of high learning achievement and being able to restate a concept. The subject is always active in every stage of learning activities. The subject of low learning achievement is less able to express money as a concept. They tend to be less active in the learning process which includes being less active in asking questions if they experience difficulties and in group discussions they still depend on friends and teacher guidance. All three subjects were able to use and utilize and select procedures to solve the perimeter and area of squares, rectangles and triangles, but experienced errors in determining the area and perimeter formulas for squares and rectangles. The subject of high learning achievement is the only subject that is able to apply the concept in problem solving. The subject uses the plan he devised to solve the problem and then communicates his conclusion correctly.Keywords: Ethnomatematics, Problem Based Learning, Understanding of Geometry ConceptsÂ ABSTRAKTujuan penelitian ini adalah mendeskripsikan pemahaman konsep geometri peserta didik kelas IV SD Negeri Candi 01 setelah implementasi model problem based learning bermuatan etnomatematika. Metode penelitian yang digunakan metode deskriptif dengan pendekatan kualitatif. Pemilihan subyek penelitian dipilih dengan teknik purposive sampling berdasarkan prestasi belajar peserta didik, yang digolongkan menjadi tiga prestasi belajar tinggi, sedang dan rendah. Subjek prestasi belajar tinggi dan sedang mampu dalam menyatakan ulang sebuah konsep. Subjek selalu aktif dalam setiap tahapan kegiatan pembelajaran. Subjek prestasi belajar rendah kurang mampu dalam menyatakan uang sebuah konsep. Mereka cenderung kurang aktif dalam proses pembelajaran yang meliputi kurang aktif dalam bertanya jika mengalami kesulitan dan dalam diskusi kelompok masih bergantung pada teman dan bimbingan guru. Ketiga subjek mampu menggunakan dan memanfaatkan serta memilih prosedur untuk menyelesaikan keliling dan luas persegi, persegi panjang dan segitiga, tetapi mengalami kesalahan dalam menentukan rumus luas dan keliling persegi dan persegi panjang. Subjek prestasi belajar tinggi merupakan satu-satunya subjek yang mampu mengaplikasikan konsep dalam pemecahan masalah.Â  Subjek menggunakan rencana yang dibuat untuk menyelesaikan masalah, lalu mengkomunikasikan kesimpulannya dengan benar.Kata kunci: Etnomatematika, Pemahaman Konsep Geometri, Problem Based Learning